1997
DOI: 10.1063/1.366227
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of high energy 120Sn implantation in GaAs

Abstract: Single crystal n-GaAs substrates have been implanted at room temperature with 120Sn ions at an energy of 70 MeV. The optical microscope and scanning electron microscope studies of the cross section of the implanted samples have shown the formation of two sharp layers at a depth of 8.7 and 11 μm from the surface of the substrate. The electrical characteristics of the Schottky diodes fabricated on the implanted substrates at room temperature indicate the presence of high series resistance due to radiation defect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…It has been demonstrated that the minority carrier life time can be reduced significantly by introducing deep level defects in Si and it is possible to improve the switching characteristics of the diodes [17].…”
Section: Electronic Devicesmentioning
confidence: 99%
“…It has been demonstrated that the minority carrier life time can be reduced significantly by introducing deep level defects in Si and it is possible to improve the switching characteristics of the diodes [17].…”
Section: Electronic Devicesmentioning
confidence: 99%
“…For the annealing temperatures 623 and 723 K the sheet resistivity increases and the sheet carrier concentration decreases. This may be due to 7 Li occupying the indium 162 N. Dharmarasu et al 7 Li and/or interaction of 7 Li with defects in general displacing 7 Li from its interstitial position. There was only a small decrease in the mobility of the implanted samples and annealing causes little increase in the mobility.…”
Section: Resultsmentioning
confidence: 99%
“…In germanium and silicon, 7 Li acts as a shallow interstitial donor and it has large diffusion coefficients [1]. However, it shows a different behavior in GaAs either as a donor or as an acceptor according to the type of conduction.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations